Effect Of Temperature Towards Membrane Fouling By Microalgae Algal Organic Matter - Salleh, Nabihah Mat (Universiti Sains Malaysia, 2022)
Membrane distillation processes deal with the temperature changes and operate at low temperatures, allowing excess heat or inferior heat sources to be used. However, membrane fouling happens when the algal organic matter (AOM) accumulates on the membrane's surface, reducing the membrane's permeability and increasing filter resistance. For the purpose of this thesis, algae organic matter (AOM) was separated into soluble extracellular polymeric substance (sEPS), and bounded extracellular polymeric substance (bEPS) / internal organic matter (IOM) from two different species (Chlorella sp. and Navicula sp.) were heated with PP hollow fibre membrane to a temperature range that was designed to simulate the MD process. The results show that both species' sEPS and bEPS / IOM had a higher percentage of carbohydrates than proteins. The temperature affected the concentration of carbohydrates and protein produced in EPS. From contact analysis, the most hydrophilic PP hollow fibre membrane in sEPS and bEPS / IOM for Chlorella sp. at temperature 80℃. While, for Navicula sp., the most hydrophilic PP hollow fibre membrane in sEPS and bEPS / IOM at temperatures 70℃ and 80℃. The morphology analysis indicates that internal fouling and external fouling occurred for both species in sEPS and bEPS / IOM. The internal and external fouling was caused by the build-up of an organic, inorganic and biological substance. Chlorella sp. species were identified as the most potentially foul MD based on EPS production, contact angle, CA analysis and scanning electron microscopy, SEM analysis.